Efficacy and safety of desmoteplase in acute ischemic stroke patients: A systematic review and meta-analysis. Issue 18 (May 2017) - Li, Xiaoqiang; Ling, Li; Li, Chuqiao; Ma, Qiujie
Abstract: Background: Pending results from double-blind, multicenter, parallel-group, randomized trials, the benefit and safety of the novel plasminogen activator, desmoteplase remain undetermined. The aim of this meta-analysis was to help evaluate desmoteplase's efficacy and safety. Methods: A thorough search was performed of the Cochrane Library, PubMed, and Embase from the inception of electronic data to March 2017, and double-blind, multicenter, parallel-group, randomized trials were chosen. We conducted a meta-analysis of studies investigating intravenous desmoteplase treatment of acute ischemic stroke patients 3 to 9 hours after symptom onset. Asymptomatic intracerebral hemorrhage, good clinical outcome at 90 days, and reperfusion 4 to 8 hours posttreatment were variables assessing efficacy; symptomatic intracerebral hemorrhage and death rates were measures of safety. Results: Six trials involving 1071 patients thrombolyzed >3 hours postonset were included (600 received intravenous desmoteplase, 471 placebo). Desmoteplase was associated with increased reperfusion (odds ratio [OR] 1.57; 95% confidence interval [CI], 1.10–2.24; P = .01 vs control) and showed a tendency to increase asymptomatic intracerebral hemorrhage (OR 1.25; 95% CI, 0.97–1.62; P = .09 vs control), whereas there was no increase in symptomatic intracerebral hemorrhage and death rate with desmoteplase. However, there was no difference in the clinical response at 90 days (OR 1.14; 95% CI, 0.88–1.49; P = .31 vs control). Subgroup analysis showed that desmoteplase 90 μg/kg (OR 1.53; 95% CI, 1.07–2.21; P = .02 vs control) and 125 μg/kg (OR 4.07; 95% CI, 1.16–14.24; P = .03 vs control) were associated with an increase in reperfusion. Also, we found desmoteplase 90 μg/kg showed a tendency to increase asymptomatic intracerebral hemorrhage (OR 1.25; 95% CI, 0.95–1.63; P = .11 vs control). Conclusion: Intravenous desmoteplase is associated with a favorable reperfusion efficacy and acceptable safety in ischemic stroke treatment >3 hours after symptom onset. Well-designed randomized controlled trials with larger patient cohorts and a moderate dose of drugs are needed to further evaluate the true efficacy of desmoteplase in stroke patients. Trial Registration: URL:http://www.crd.york.ac.uk/PROSPERO ; PROSPERO registration number: CRD42016037667). Abstract : Supplemental Digital Content is available in the text